Retail banking in the context of digital transformation: modern trends, institutional challenges and development prospects ("Journal "U". Economy. Management. Finance.", 2025)
Retail banking covers a wide range of financial services for the population – from opening accounts and payments to lending and savings products. In recent years, the retail banking sector has undergone rapid changes under the influence of digitalization, innovative technologies and changing consumer behavior. At the same time, banks face new challenges, including increased regulatory oversight, cybersecurity requirements and competition from fintech companies and IT giants. The article consistently examines the current situation and development trends of the Russian retail banking market, the role of modern technologies, changes in customer behavior, as well as the problems and challenges facing banks.
Keywords: banking services; consumer behavior; digital threats; digital risks; fintech; online services; digital economy